DIET WITH CHOCOLATE OR BLACK TEA? IS IT EFFECTIVE? - Elvina Astiningtyas Sudaryanto; Hesti Triwahyu Hutami; Nyoman Suci Widiastiti; Endang Mahati (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Introduction: Based on national research 2018, in Indonesia, 21% of population is obesed. Obesity can lead to various metabolic Syndrome. The consumption of Chocolate and Black Tea can decrease insulin. BMI and Fasting Blood Glucose is use as an assessment to observe the effectivity of Chocolate and Black tea as a method of diet. Methods: This experimental study used pre and post-test control group design. Eighteen male BALB/c obese mice were randomly divided into three groups. Control group did not receive anything, 1st group treated with black tea extract, while 2nd group treated with chocolate extract. Data, such as body weight and glucose fasting level was acquired weekly. Fasting Blood Glucose was assessed with accu check. Data normality were tested using Saphiro-Wilk test. Then, Kruskall-Wallis was employed to determine whether the means of each groups differ significantly. Results: The average weight in P2 groups (31,75±3,40 gram) was significantly lower than Control (36,50±1,97 gram p=0.03) but not significantly lower than P1 (34,40±1,14 gram p=0.137) group. The average weight in P1 was not significantly lower than Control (p=0.089). There was no significant change of number in the average Glucose fasting level (p=0.21). Conclusion : Chocolate and Black Tea could affect body weight, but could not effect fasting blood glucoseKeyword: Black Tea, BMI, Body weight, Ch ocolate, Glucose fasting level